2018
DOI: 10.1038/s41598-018-26914-3
|View full text |Cite
|
Sign up to set email alerts
|

Toxic effects of selected proprietary dry eye drops on Acanthamoeba

Abstract: Amoebae of the genus Acanthamoeba are ubiquitous protists that have been isolated from many sources such as soils, water and the air. They are responsible for infections including fatal encephalitis and a severe keratitis in humans. To date, there is no satisfactorily effective therapeutic agent against this pathogen and the infections it causes are exacerbated by the existence of a resistant cyst stage produced by this amoeba. As dry eye syndrome is a risk factor for Acanthamoeba keratitis, we aimed to evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 22 publications
(26 reference statements)
1
20
0
Order By: Relevance
“…Programmed Cell Death (PCD) has been previously reported in our laboratory in Acanthamoeba genus after incubation with compounds such as statins and voriconazole among other molecules 2,27,28 . The process of PCD involves multiple changes such as chromatin condensation, cell shrinkage and loss of mitochondrial potential among other phenomena 29 .…”
Section: Discussionmentioning
confidence: 91%
“…Programmed Cell Death (PCD) has been previously reported in our laboratory in Acanthamoeba genus after incubation with compounds such as statins and voriconazole among other molecules 2,27,28 . The process of PCD involves multiple changes such as chromatin condensation, cell shrinkage and loss of mitochondrial potential among other phenomena 29 .…”
Section: Discussionmentioning
confidence: 91%
“…The experiment was carried out by following the manufacturer's recommendations, and 5 × 10 5 cells/ml well were incubated in a 96-well plate for 24 h with the previously calculated IC 90 . As it has been previously reported 52 , the double-staining pattern allows the identification of three groups in a cellular population: live cells will show only a low level of fluorescence, cells undergoing PCD will show a higher level of blue fluorescence (as chromatin condenses), and dead cells will show low-blue and high-red fluorescence (as the Propidium Iodide stain enters the nucleus).…”
Section: Double-stain Assay For Programmed Cell Death Determination mentioning
confidence: 78%
“…Both of these compounds have been reported to be effective against different bacteria species [18,19] and, on the other hand, propylene glycol also presents a remarkable preservative effect [20,21]. A previous study from our laboratory has shown the anti- Acanthamoeba activity of Systane ® Ultra and its induction of programmed cell death (PCD) mechanism [16]. In addition, the presence of a POLYQUAD ® , which has been demonstrated as capable to activate and elevate the secretion of inflammation markers, is a disadvantage in the ocular use of Systane ® Ultra.…”
Section: Discussionmentioning
confidence: 99%
“…The in vitro effect of Systane ® Ultra and Naviblef ® Daily Care against the three tested Acanthamoeba strains ( A. castellanii Neff, A. polyphaga (ATCC ® 30461™) and A. griffini ), was evaluated using a colorimetric assay based on the alamarBlue TM Cell Viability Reagent (Invitrogen by Thermo Fisher Scientific), as it has previously described [7,16,26,27]. As first step, the Acanthamoeba culture was seeded in triplicate on a 96-well microtiter plates (50μL from a stock solution of 5 × 10 4 cells/mL).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation